2014
DOI: 10.1128/jvi.00539-14
|View full text |Cite
|
Sign up to set email alerts
|

The Rhinovirus Subviral A-Particle Exposes 3′-Terminal Sequences of Its Genomic RNA

Abstract: Enteroviruses, which represent a large genus within the family Picornaviridae, undergo important conformational modifications during infection of the host cell. Once internalized by receptor-mediated endocytosis, receptor binding and/or the acidic endosomal environment triggers the native virion to expand and convert into the subviral (altered) A-particle. The A-particle is lacking the internal capsid protein VP4 and exposes N-terminal amphipathic sequences of VP1, allowing for its direct interaction with a li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 64 publications
(56 reference statements)
2
20
1
Order By: Relevance
“…The immunoprecipitation assay included a crosslink to stabilize protein-RNA complexes, and to prevent myosin Va from dissociating from the BrU-RV-B14 genome during the procedure 71 . Our observations of uncoated BrU-RNA (Figs 3 and 4 ) did not exclude the possibility that we actually detected A-particles with partially released RNA 72 . Nevertheless, our data strongly argue that myosin Va was playing an essential role in the release of the RV-B14 genome.…”
Section: Discussioncontrasting
confidence: 58%
“…The immunoprecipitation assay included a crosslink to stabilize protein-RNA complexes, and to prevent myosin Va from dissociating from the BrU-RV-B14 genome during the procedure 71 . Our observations of uncoated BrU-RNA (Figs 3 and 4 ) did not exclude the possibility that we actually detected A-particles with partially released RNA 72 . Nevertheless, our data strongly argue that myosin Va was playing an essential role in the release of the RV-B14 genome.…”
Section: Discussioncontrasting
confidence: 58%
“…In particular, transfection of viral RNA bypasses normal cellular receptor-mediated entry pathways. It is likely that the uncoating of the vRNA following a normal infection determines the cytoplasmic delivery site of the vRNA and which end of the vRNA is initially exposed to the cytoplasm ( 37 ). To circumvent this potential limitation, we generated MEF-TDP2 +/+ and MEF-TDP2 −/− cell lines stably expressing the human poliovirus receptor (PVR) ( 38 , 39 ) under blasticidin selection.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was demonstrated that RNA exit starts from the 3’-end on heating to 56 °C in vitro [ 155 ], as well as on physiologic endosomal acidification in vivo [ 156 ]. Interestingly, upon acidification in vitro , exit halted after about 700 bases had egressed.…”
Section: Uptake and Uncoating Of The Minor Receptor-group Prototype Rmentioning
confidence: 99%